Hepatoprotective Effects of Schleichera oleosa Leaf Extract on TGF-β Expression and Liver Fibrosis in CCl₄-Induced Rat Model - Tias Pramesti Griana; Kholifah Holil; Andrean Vicki; Aathifah Aathifah; Anik Listiyana (El-Hayah:Jurnal Biologi, 2026)
CCL4 exposure on rat resulted hepatocyte cell necrosis and activated macrofages to produce TGF-β which induced liver fibrosis. Kesambi (Schleichera oleosa (Lour.) Oken) plants have active compounds that affect the inflammatory process. The purpose of this study was to determine the effects of methanol leaf extracts from Kesambi on TGF-β levels and histologycal feature of liver in rat exposed to CCL4. Thirty male Wistar rat were divided into 5 groups, K- (injected with corn oil i.p), K+ (injected with CCL4 0,5µl/grb.w. i.p, 2x a week), and the treatment group injected with CCL4 0,5µl/grb.w. i.p, 2x a week and administrated methanol leaf extracts from kesambi dose 200mg/kgb.w. (P1), 400mg/kgb.w. (P2), and 600mg/kgb.w. (P3), everyday. After 6 weeks, the rats were dissected. Liver was taken for TGF-β levels measurement by flowcytometri, necrotizing hepatocyte cells calculation and fibrosis score by METAVIR method. TGF-β level of P3 (4,21%) was significantly different (p0,05) compared to K- (6,34%), K+ (7,21%), P1 (7,80%), and P2 (8,45%). The number of cell necrosis of K+ (54,39%) was significantly different from K- (9,62%), P2 (29,37%), and P3 (18,75%). METAVIR score calculation showed fibrosis in K+ (score 2), P1 (score 2), and P2 (score 1). The administration of methanol leaf extracts from kesambi reduced TGF-β levels and the number of necrotic hepatocyte cells and prevented the formation of liver fibrosis.